The big book of presentation games: wake-em-up tricks, ice breakers & other fun stuff - Newstrom, John W.; Scannell, Edward E. (Paris, 1998)
"Don't let the audience snooze through any of your presentations! How do you keep an audience from becoming bored or restless during a presentation? Find out with The Big Book of Presentation Games. Each game in The Big Book of Presentation Games is fast, fun, creative, and easy-to-read, and easy-to-lead, and costs little or nothing. Categories also include: great session-openers; icebreakers; climate-setting games; practical jokes and tricks; audience brainteasers; motivation activities; memorable closing activities; and much more!"